Bone Marrow Aspiration Concentrate and Platelet Rich Plasma for Osteochondral Repair in a Porcine Osteochondral Defect Model - Schneppendahl, Johannes; Thuns, Simon; Herten, Monika; Sager, Martin; Jungbluth, Pascal; Hakimi, Mohssen; Wild, Michael; Betsch, Marcel (PLoS ONE, 2013)
Background:Bone marrow aspiration concentrate (BMAC) may possess a high potency for cartilage and osseous defect healing because it contains stem cells and multiple growth factors. Alternatively, platelet rich plasma (PRP), which contains a cocktail of multiple growth factors released from enriched activated thrombocytes may potentially stimulate the mesenchymal stem cells (MSCs) in bone marrow to proliferate and differentiate.Methods:A critical size osteochondral defect (10×6 mm) in both medial femoral condyles was created in 14 Goettinger mini-pigs. All animals were randomized into the following four groups: biphasic scaffold alone (TRUFIT BGS, Smith & Nephew, USA), scaffold with PRP, scaffold with BMAC and scaffold in combination with BMAC and PRP. After 26 weeks all animals were euthanized and histological slides were cut, stained and evaluated using a histological score and immunohistochemistry.Results:The thrombocyte number was significantly increased (p = 0.049) in PRP compared to whole blood. In addition the concentration of the measured growth factors in PRP such as BMP-2, BMP-7, VEGF, TGF-β1 and PDGF were significantly increased when compared to whole blood (p<0.05). In the defects of the therapy groups areas of chondrogenic tissue were present, which stained blue with toluidine blue and positively for collagen type II. Adding BMAC or PRP in a biphasic scaffold led to a significant improvement of the histological score compared to the control group, but the combination of BMAC and PRP did not further enhance the histological score.Conclusions:The clinical application of BMAC or PRP in osteochondral defect healing is attractive because of their autologous origin and cost-effectiveness. Adding either PRP or BMAC to a biphasic scaffold led to a significantly better healing of osteochondral defects compared with the control group. However, the combination of both therapies did not further enhance healing. © 2013 Betsch et al.
CRIS-Team Scopus Importer:2022-07-20